Microstructures and properties of the dissimilar joint of pure molybdenum/T2 copper by single-mode laser welding. (December 2021) - Zhou, Xian-Rong; Ning, Jie; Na, Suck-Joo; Zhang, Lin-Jie
Abstract: The fusion welding of molybdenum (Mo) and copper (Cu) is challenging task due to significant differences between chemical composition and physical properties of the two metals. A sound quality laser beam welding (LBW) joint between Mo and Cu is developed through the addition of pure Ni as an interlayer and laser beam offsetting. The evolution of microstructure in weld zone (WZ) and its impact on joint performance is analyzed through scanning electron microscope (SEM), energy dispersive spectrometer (EDS), electron backscattered diffraction (EBSD), tensile and hardness test. At room temperature, the LBW joint between Mo and Cu is ruptured from heat affect zone (HAZ) near fusion zone (FZ) under a tensile load of 209 MPa. The addition of Ni as interlayer between LBW joint of Mo and Cu contributed an increase of 37.79% in tensile strength and the joint is ruptured from HAZ beside the base material Cu. Such improvement in joint performance is attributed to grain refinement in FZ, coarsening of transition zone (TZ) between Mo and Cu and directional solidification towards Cu rich region in FZ due to addition of Ni into LBW joint between Mo and Cu. The research results provide reference for the welding between dissimilar materials with significantly different melting points. Highlights: The reliable Cu/Mo dissimilar joint was successfully welded by using beam offset and the addition of a Ni foil. The influences of the laser beam offset and the addition of Ni foil on the Cu/Mo dissimilar joint were analyzed. The addition of Ni foil increases the tensile strength of the joint by about 38%. Grain refinement of FZ, solid solution strengthening effect contributed to the improvement of tensile strength of the joint.